Epidemiological insights from a large-scale investigation of intestinal helminths in Medieval Europe. - Patrik G Flammer; Hannah Ryan; Stephen G Preston; Sylvia Warren; Renáta Přichystalová; Rainer Weiss; Valerie Palmowski; Sonja Boschert; Katarina Fellgiebel; Isabelle Jasch-Boley; Madita-Sophie Kairies; Ernst Rümmele; et al. (Public Library of Science (PLoS), 2020)
Helminth infections are among the World Health Organization's top neglected diseases with significant impact in many Less Economically Developed Countries. Despite no longer being endemic in Europe, the widespread presence of helminth eggs in archaeological deposits indicates that helminths represented a considerable burden in past European populations. Prevalence of infection is a key epidemiological feature that would influence the elimination of endemic intestinal helminths, for example, low prevalence rates may have made it easier to eliminate these infections in Europe without the use of modern anthelminthic drugs. To determine historical prevalence rates we analysed 589 grave samples from 7 European sites dated between 680 and 1700 CE, identifying two soil transmitted nematodes (Ascaris spp. and Trichuris trichiura) at all locations, and two food derived cestodes (Diphyllobothrium latum and Taenia spp.) at 4 sites. The rates of nematode infection in the medieval populations (1.5 to 25.6% for T. trichiura; 9.3-42.9% for Ascaris spp.) were comparable to those reported within modern endemically infected populations. There was some evidence of higher levels of nematode infection in younger individuals but not at all sites. The genetic diversity of T. trichiura ITS-1 in single graves was variable but much lower than with communal medieval latrine deposits. The prevalence of food derived cestodes was much lower (1.0-9.9%) than the prevalence of nematodes. Interestingly, sites that contained Taenia spp. eggs also contained D. latum which may reflect local culinary practices. These data demonstrate the importance of helminth infections in Medieval Europe and provide a baseline for studies on the epidemiology of infection in historical and modern contexts. Since the prevalence of medieval STH infections mirror those in modern endemic countries the factors affecting STH decline in Europe may also inform modern intervention campaigns.